Use of long acting antipsychotics and relationship to newly diagnosed bipolar disorder: a pragmatic longitudinal study based on a Canadian health registry - Emmanuel Stip; Syed Javaid; Jonathan Bayard-Diotte; Karim Abdel Aziz; Danilo Arnone (SAGE Publishing, 2020)
Background: There is limited data from large naturalistic studies to inform prescribing of long-acting injectable medication (LAIs). Guidance is particularly rare in the case of primary mood disorders. Methods: This study describes prescribing trends of LAIs in 3879 patients in Quebec, Canada, over a period of 4 years. Health register data from the Quebec provincial health plan were reviewed. Results: In this specific registry, 32% of patients who received LAIs drugs for schizophrenia had a confirmed diagnosis of bipolar disorder and 17% had a diagnosis of major depressive disorder. Non-schizophrenia syndromes were preferentially prescribed risperidone long-acting antipsychotic, whereas patients with schizophrenia were prescribed an excess of haloperidol decanoate. Patients with non-schizophrenia disorders prescribed long-acting antipsychotics were more frequently treated in primary care compared with patients with schizophrenia. Conclusion: Data from a large number of patients treated naturalistically in Quebec with long-acting antipsychotics suggests that these compounds, prescribed to treat symptoms of schizophrenia and schizoaffective disorders, were maintained when mood symptoms emerged, even in cases when the diagnosis changed to bipolar disorder. This pragmatic study supports the need to explore this intervention as potential treatment for affective disorders.